PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN ANGGOTA (Studi pada Koperasi Simpan Pinjam Langgeng Makmur Surabaya) - Muhajir, Ali (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2015)
This research take a title the Influences of service quality and Consumer Value Toward Member Satisfaction of Langgeng Makmur Cooperation which moved in lend and borrow financial service. This research purpose to recognize how variable role of service quality and consumer value  in order to increase member satisfaction of Langgeng Makmur Cooperation Surabaya. From both independent variables that are service quality and consumer value which one is dominantly role increasing satisfaction of cooperation member.            Data collected through questionnaire method toward 74 respondents or service user of Langgeng Makmur cooperation Surabaya that gained by using Simple Random Sampling technique. Analysis that used is multiple linear regression analysis with computer software aided SPPS 20.00.            From the analysis yield can be concluded that service quality variable and consumer value simultaneously have influence toward satisfaction level of member Langgeng Makmur cooperation Surabaya. It is compatible with hypothesis posed, get proved with calculation result by using multiple linear regression method where gained value R2  as high 0,715 or 71,50% member satisfaction influenced by service quality and consumer value variables while the rest is 28,5% influenced with other factor that uncalculated in this research. Then from both independent variables researched that are service quality and consumer value, based on variable t-test or partial test can be concluded that most dominant which influence member satisfaction level in Langgeng Makmur cooperation Surabaya  is service quality variabel, where it can be proved with regression value between service quality variable and member satisfaction as many 0,642 or 64,20% member satisfaction influenced by service quality in assumption value consumer is nil and correlation value as 0,801 or 80,10% with significant level 0,000 or far under alpha value as 0,05 or 5%.